Relationship of potato yield and factors of influence on the background of herbological protection - Shuvar Ivan; Korpita Hanna; Shuvar Antin; Shuvar Bogdan; Balkovskyi Volodymyr; Kosylovych Halyna; Dudar Ivan (Open Agriculture, 2022)
The latest technologies for growing crops, including potatoes, are based on the use of modern mathematical models that can fairly accurately identify the impact of various factors of natural and technological nature on the object of study. Yield modeling makes it possible to adjust resource consumption indicators to obtain the maximum economic effect and minimize the negative impact on the environment. It was found that the lowest weediness of potato agrocenosis (24 pcs/m2) was formed by the complex application of Hezagard (4 L ha−1) and Panthera (1 L ha−1). The lowest level of actual weeds infestation had a positive effect on the yield of tubers – 27.6 t ha−1 (+26.6% to control) and was obtained in the variant of herbicide application. The results of correlations of potato tuber yield from factors such as weediness, density and productive moisture reserves in the arable soil layer are highlighted. It was found that the highest yield of 27.6 t ha−1 (+26.6% compared to the control) was obtained in the variant with the application of herbicides Hezagard (4 L ha−1) and Panthera (1 L ha−1). According to the results of multiple regression, it was found that the coefficient of multiple correlation is R = 0.9985, and the coefficient of determination is R = 0.997, i.e., the relationship between potato yield and experimental factors is quite close.